Kerjasama Indonesia-Kamboja dalam sektor pariwisata melalui hubungan bilateral dan organisasi wilayah ASEAN Tahun 1955-2018 - Naufal Mubarok Akhmad; Yuliati Yuliati (Universitas Negeri Malang, 2022)
Tourism is an important sector to support the economy of a country because the contribution of foreign exchange from tourism is very high. Cambodia as one of the countries in the Southeast Asian region that is trying to provide the widest possible employment opportunities for its population and in order to improve the country's economy can certainly make tourism as a way out. Supported by the potential for abundant cultural diversity and attractive natural beauty, Cambodia must certainly advance the tourism sector. With the cooperation, one of which is from the ASEAN Tourism Forum (ATF) it is very helpful for Cambodia to promote its tourism. Indonesia, which is part of it, of course, intervenes in helping Cambodia advance the tourism sector through sharing cooperation. UNESCO’s cultural heritage in Cambodia and Indonesia, namely Angkor Wat Temple and Borobudur Temple, is used as a tourism sector cooperation to invite many tourists. The collaborations include labor training, cooperation between entrepreneurs, and tourism marketing cooperation between the two countries. Pariwisata menjadi sektor yang penting untuk menunjang perekonomian suatu negara karena sumbangan devisa negara dari pariwisata sangatlah tinggi. Kamboja sebagai salah satu negara dikawasan Asia Tenggara yang berusaha memberikan lapangan pekerjaan seluas-luasnya bagi penduduknya serta demi meningkatkan perekonomian negaranya tentu bisa menjadikan pariwisata sebagai jalan keluar. Dengan didukung oleh potensi keragaman budaya yang melimpah serta keindahan alam yang memikat tentunya harus menjadikan Kamboja untuk memajukkan sektor pariwisata. Dengan adanya kerjasama salah satunya dari ASEAN Tourism Forum (ATF) sangatlah membantu Kamboja dalam mempromosikan pariwisatanya. Indonesia yang jadi bagian di dalamnya tentunya ikut turun tangan dalam membantu Kamboja memajukan sektor pariwisata melalui berbagi kerjasama. Warisan budaya UNESCO di Kamboja dan Indonesia yaitu Candi Angkor Wat dan Candi Borobudur dijadikan sebagai kerjasama sektor pariwisata untuk mengundang banyak wisatawan. Kerjasama yang dijalin antara lain pelatihan tenaga kerja, menjalin kerjasama antar pengusaha, serta kerjasama pemasaran wisata kedua negara.